THE BRAZIL OF LULA: A GLOBAL AND AFFIRMATIVE DIPLOMACY (2003-2010) - Visentini, Paulo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
During Lula’s government (2003-2010) Brazil experienced significant social and economical improves, but especially developed an “active and affirmative” diplomacy of global span, which assured autonomy and international prestige. Beneath Brazil’s coordination the South American integration had moved on. The country established strategic partnerships with China, Russia, India and South Africa, which, added to the advance of the south-south cooperation, changed the course of global multilateral negotiation. When it is about to choose the heiress, Lula’s diplomatic legacy must deepen, contributing to a worldwide reform.